Measuring Violence Behaviours in the Context of Romantic Relationships during Adolescence: New Evidence about the Modified Conflict Tactics Scale - Javier Ortuño-Sierra; Natalia Marugán Garrido; Andrea Gutiérrez García; Ana Ciarreta López; Tomas Camara-Pastor (MDPI AG, 2023)
The main purpose of the present study was to analyze the psychometric properties of the Spanish version of the Modified Conflict Tactics Scale (M-CTS) in adolescents. The M-CTS is a questionnaire that screens for intimate partner violence. Additionally, we studied the association between the M-CTS and attitudes towards violence. The study included a sample of 1248 students in a cross-sectional survey. The M-CTS and the Attitudes Towards Violence (EAV) scale were used. The analysis of the internal structure of the M-CTS revealed that a four-factor structure was the best fitting solution. The M-CTS scores revealed evidence of structural equivalence by gender and age. The McDonald's Omega indices were adequate for both victims and perpetrators models. Moreover, attitudes towards violence were positively correlated with measures of violence manifestations. Results found in the present study confirm the psychometric adequacy of the M-CTS scores and gather new evidence about its internal structure and measurement equivalence for its use in samples of adolescent and young students. The assessment of intimate partner violence may contribute to detect adolescents at risk for different forms of violence in the future.